A Liouville type theorem for axially symmetric D-solutions to steady Navier–Stokes equations. (October 2019) - Zhao, Na
Abstract: We study axially symmetric D -solutions of three dimensional steady Navier–Stokes equations. We prove that if the velocity u decays like | x ′ | − ( 2 3 ) + uniformly for z, or the vorticity ω decays like | x ′ | − ( 5 3 ) + uniformly for z, then u vanishes. Here | x ′ | denotes the distance to the axis.